1997
DOI: 10.1017/s0094837300016638
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic speciation in the living planktonic foraminiferGlobigerinella siphonifera(d'Orbigny)

Abstract: Abstract.-Two living forms of Globigerinella siphonifera (d'Orbigny), presently identified as Type I and Type II, can easily be distinguished and collected by SCUBA divers because of differences in appearance, arrangement of the rhizopodial network, and the presence or absence of commensals. Additional biological differences are apparent from laboratory culture experiments; Type I individuals survive significantly longer than Type II under conditions of darkness and starvation and have significantly slower cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
119
2
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(134 citation statements)
references
References 60 publications
6
119
2
5
Order By: Relevance
“…However, it is quite possible that shell morphology may not be a true measure of planktic foraminiferal diversity. It has been demonstrated that two distinct genotypes of Globigerinella siphonifera cannot be discriminated morphologically without close analysis of test ultrastructure [Huber et al, 1997]. Clear genetic differences can be identified between genotypes in such cryptic speciation events.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is quite possible that shell morphology may not be a true measure of planktic foraminiferal diversity. It has been demonstrated that two distinct genotypes of Globigerinella siphonifera cannot be discriminated morphologically without close analysis of test ultrastructure [Huber et al, 1997]. Clear genetic differences can be identified between genotypes in such cryptic speciation events.…”
Section: Introductionmentioning
confidence: 99%
“…In planktonic foraminifera, heritability has yet to be measured for any morphological trait, although it is likely to vary amongst traits as it does in all other organisms studied to date (Visscher et al, 2008). In this context, it is interesting to note that genetic-species of planktonic foraminifera are often found in distinct environments (i.e., different biomes or different depth habitats) (Huber et al, 1997;de Vargas et al, 2001;Darling & Wade, 2008;Morard et al, 2009;Quillévéré et al, 2011;Morard et al, 2013;Morard et al, 2016). While evidence for high heritability of wall thickness and porosity is lacking, both 325 porosity and wall thickness have been observed to vary with environmental conditions in culture and across environments gradients (this study; Colombo & Cita, 1980;Caron, 1987a-b;Bijma et al, 1990;Lea et al, 1999;Spero et al, 1997;Russell et al, 2004;Lombard et al, 2009;Kuroyanagi et al, 2013;Spero et al, 2015;Henehan et al, 2017).…”
Section: Discussionmentioning
confidence: 67%
“…This raises the interesting possibility that some of the morphological differences between different genetic species are driven primarily by differences in the environment in which they occur, rather than by heritable genetic differences. While 330 explanations of ecophenotypy have been dismissed in the past (Huber et al, 1997;Morard et al, 2009), our results suggest it should be seriously considered, at least for some traits like porosity, going forward.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations